2001
DOI: 10.1067/mtc.2001.116560
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of surgical resection and adjuvant high-dose hemithoracic radiation for malignant pleural mesothelioma

Abstract: Hemithoracic radiation after complete surgical resection at a dose not previously reported is feasible. This approach dramatically reduces local recurrence and is associated with prolonged survival for early-stage tumors. Stage III disease has a high risk of early distant relapse and should be considered for trials of systemic therapy added to this regimen of resection and radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
264
2
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(277 citation statements)
references
References 34 publications
1
264
2
10
Order By: Relevance
“…This is more easily performed after EPP than P/D as there is an empty cavity without remaining lung parenchyma. In a phase II trial of 57 patients undergoing EPP or P/D, a postoperative dose of 54 Gy was administered [34]. Local recurrence was 13% with a median survival time of 17 months, which was lower than historical series.…”
Section: Combined-modality Therapymentioning
confidence: 99%
“…This is more easily performed after EPP than P/D as there is an empty cavity without remaining lung parenchyma. In a phase II trial of 57 patients undergoing EPP or P/D, a postoperative dose of 54 Gy was administered [34]. Local recurrence was 13% with a median survival time of 17 months, which was lower than historical series.…”
Section: Combined-modality Therapymentioning
confidence: 99%
“…EPP removes radiation-sensitive lung, so it permits the delivery of higher postoperative doses to the involved hemithorax. A phase II trial conducted at the Memorial Sloan-Kettering Cancer Center demonstrated that a high dose of hemithoracic radiation (54 Gy) following EPP was well tolerated with reduced local recurrence rates and prolonged survival for early-stage MPM [35]. A new solution that produces more conformal dose distributions by saving critical structures is provided by intensity-modulated radiotherapy (IMRT) [36].…”
Section: Radiotherapy For Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…Radiotherapy has often been added to surgery in an attempt to improve local control. It is used as adjuvant therapy after EPP as part of trimodality treatment, which is effective at reducing local recurrence of the tumor and improving overall survival [35].…”
Section: Radiotherapy For Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…One of the potential intraoperative complications of EPP is hemorrhage, which is associated with a high rate of perioperative transfusions (approximately 90%) [72,74]. Surgeryassociated hemorrhage complicates the postoperative period, frequently requiring reoperation for control of surgical bleeding [72,73].…”
Section: Extrapleural Pneumonectomy For Malignant Pleural Mesotheliomamentioning
confidence: 99%